Action Comics : 80 years of Superman - Siegel, Jerry, 1914-1996; Shuster, Joe, 1914-1992 (DC Comics, 2018)
Classic Superman stories spanning 1938 to 2012 and including the first appearances of Supergirl, Brainiac, the Fortress of Solitude, and others..